How to screen a paediatric elbow X-ray for injuries - Brian Madison; Patrick Tshizubu (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
Elbow injuries are common in the paediatric population. Diagnosing these injuries relies on X-rays taken on initial presentation in the emergency department. Interpreting these radiographs can occasionally be challenging, partly because of the sequential appearance of secondary ossification centres in the paediatric elbow. We propose a methodical approach that would help a clinician identify these injuries, especially the radiographically subtle ones. Evaluating these X-rays should start with a lateral view which identifies the majority of elbow injuries. Anterior cortical disruption, fat pad sign, and the anterior humeral line can be evaluated on this view, and if present, alerts the clinician to a possible subtle fracture. On this view also, the clinician can evaluate the radio-capitellar line and then proceed to evaluate it again on the anteroposterior view. With this approach almost all fractures and dislocations around the elbow can be identified.